Methodology for in-game certification in serious games - Baptista, Ricardo (2013)
Serious games are starting to attain a higher role as tools for learning in various contexts, but in particular in areas such as education and training. Due to its characteristics, such as rules, behavior simulation and feedback to the player's actions, serious games provide a favorable learning environment where errors can occur without real life penalty and students get instant feedback from challenges. These challenges are in accordance with the intended objectives and will self-adapt and repeat according to the student’s difficulty level. Through motivating and engaging environments, which serve as base for problem solving and simulation of different situations and contexts, serious games have a great potential to aid players developing professional skills. But, how do we certify the acquired knowledge and skills? With this work we intend to propose a methodology to establish a relationship between the game mechanics of serious games and an array of competences for certification, evaluating the applicability of various aspects in the design and development of games such as the user interfaces and the gameplay, obtaining learning outcomes within the game itself. Through the definition of game mechanics combined with the necessary pedagogical elements, the game will ensure the certification. This paper will present a matrix of generic skills, based on the European Framework of Qualifications, and the definition of the game mechanics necessary for certification on tour guide training context. The certification matrix has as reference axes: skills, knowledge and competencies, which describe what the students should learn, understand and be able to do after they complete the learning process. The guides-interpreters welcome and accompany tourists on trips and visits to places of tourist interest and cultural heritage such as museums, palaces and national monuments, where they provide various information. Tour guide certification requirements include skills and specific knowledge about foreign languages and in the areas of History, Ethnology, Politics, Religion, Geography and Art of the territory where it is inserted. These skills are communication, interpersonal relationships, motivation, organization and management. This certification process aims to validate the skills to plan and conduct guided tours on the territory, demonstrate knowledge appropriate to the context and finally match a good group leader. After defining which competences are to be certified, the next step is to delineate the expected learning outcomes, as well as identify the game mechanics associated with it. The game mechanics, as methods invoked by agents for interaction with the game world, in combination with game elements/objects allows multiple paths through which to explore the game environment and its educational process. Mechanics as achievements, appointments, progression, reward schedules or status, describe how game can be designed to affect players in unprecedented ways. In order for the game to be able to certify tour guides, the design of the training game will incorporate a set of theoretical and practical tasks to acquire skills and knowledge of various transversal themes. For this end, patterns of skills and abilities in acquiring different knowledge will be identified.